THE HISTOLOGICAL STRUCTURE AND HISTOMORPHOMETRY OF GRANULOCYTE IN BALI CATTLE POST MINERAL ADMINISTRATION - Rahayu, Ni Luh Sri Sundari; Suwiti, Ni Ketut; Suastika, Putu (Buletin Veteriner Udayana; Vol. 8 No. 2 Agustus 2016, 2016)
The aims of this study was to describe the histologycal structure and histomorphometry of granulocyte in bali cattle post mineral administration.  A total of 24 blood samples of bali cattle  consist of three treatment groups were used in this study. Blood sampling was done through the jugular vein.  The blood slides were made using slide method performed in the field then followed by fixation and staining Hematoxilin Eosin.  Granulocyte measurements performed a microscope using a 100x magnification, and then analyzed by analysis of variant.  The structire histological analyzed by qualitative descriptive analysis.  The results showed that administration of minerals in the feed has no significant effect for histomorphometry of the neutrophils, eosinophils, and basophils cell.  In addition, there was alsos no defference of histological structure of granulocyte in between group.
Keywords: sapi bali, mineral, struktur histologi, histomorfometri granulosit, bali cattle, minerals, histological structure, histomorphometry granulocyte